The New Hampshire colony - Fradin, Dennis B. (Chicago : Childrens Press, 1988)
Traces the history of New Hampshire from the time of Indian settlements, through the arrival of the first colonists, to the ratification of the Constitution in 1788 which made it the ninth state.
Includes index.
Keywords: New Hampshire -- History -- Colonial period, ca. 1600-1775.; New Hampshire -- History -- Juvenile literature. -- Colonial period, ca. 1600-1775